Unemployment and labor force participation: A panel cointegration analysis for European countries - (:unkn) unknown (My University, 2013)
This paper investigates the long-run relationship between unemployment and labor force participation and analyzes the existence of added/discouraged worker effect, which has potential impact on economic growth and development. Using panel cointegration techniques for a panel of European countries (1983-2009), the empirical results show that this long-term relation exists for only females and there is discouraged worker effect for them. Thus, female unemployment is undercount.
Keywords: Discouraged worker effect; Economic development; Labor-force participation rate; Panel cointegration; Unemployment rate